2020
DOI: 10.1177/0957650920916285
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of base fluid type of the nanofluid on heat pipe performance

Abstract: Most recently, an ascending tendency in nanoparticles containing working fluid utilization has been observed in such thermal systems as double pipe heat exchangers and thermosiphons in so far as its advantages upon the performance of such systems. In order to investigate how the type of the base fluid affects the nanofluid’s properties used for thermal applications, an experimental test rig was setup and two different nanofluid each of which involves different base fluid, but same nanoparticles and surface act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Water and kerosene are selected to be the base fluid. The decision of selecting different base fluids is made based on the experiment performed by Yilmaz et al, [44] where they observed that the base fluids can affect the performance of heat transfer process. The thermal properties of CNTs and based liquids are depicted in Table 1 and Table 2.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Water and kerosene are selected to be the base fluid. The decision of selecting different base fluids is made based on the experiment performed by Yilmaz et al, [44] where they observed that the base fluids can affect the performance of heat transfer process. The thermal properties of CNTs and based liquids are depicted in Table 1 and Table 2.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The performance improvement rates for the system were reported as 29.5% and 13.3% for ethylene glycol-based and deionized water-based nanofluids. 19…”
Section: Introductionmentioning
confidence: 99%
“…35 Thermal performance of nanofluids with various nanoparticles are experimentally investigated by various researchers. 68 Choudhary et al 9 evaluated the efficiency of iron oxide nanofluid over a flat plate solar collector (FPSC). It was found that the efficiency of FPSC enhanced by using iron oxide nanofluid.…”
Section: Introductionmentioning
confidence: 99%